Metagenomic analysis of the fecal microbiome in colorectal cancer patients compared to healthy controls as a function of age - Jordan Kharofa; Senu Apewokin; Theresa Alenghat; Nicholas J. Ollberding (Cancer Medicine, 2023)
Abstract Background and Aims Colorectal cancer (CRC) incidence is increasing in young patients without a clear etiology. Emerging data have implicated the fecal microbiome in CRC carcinogenesis. However, its impact on young onset CRC is poorly defined. Methods We performed a meta‐analysis of fecal metagenomics sequencing data from n = 692 patients with CRC and n = 602 healthy controls from eleven studies to evaluate features of the fecal metagenome associated with CRC. We hypothesized that known carcinogenic virulence factors (colibactin, fadA) and species abundance may be differentially enriched in young CRC patients relative to older CRC patients and controls. Results Summary odds ratios (OR) for CRC were increased with the presence of colibactin (OR 1.92 95% CI 1.08–3.38), fadA (OR 4.57 95% CI 1.63–12.85), and F. nucleatum (OR 6.93 95% CI 3.01–15.96) in meta‐analysis models adjusted for age, gender, and body mass index. The OR for CRC for the presence of E.coli was 2.02 (0.92–4.45). An increase in the prevalence of Fusobacterium nucleatum (OR = 1.40 [1.18; 1.65]) and Escherichia coli (OR = 1.14 [1.02; 1.28]) per 10‐year increase in age was observed in models including samples from both CRC and healthy controls. Species relative abundance was differentially enriched in young CRC patients for five species‐Intestinimonas butyriciproducens, Holdemania filiformis, Firimicutues bacterium CAG 83, Bilophilia wadsworthia, and Alistipes putredinis. Conclusion In this study, we observed strong associations with CRC status for colibactin, fadA, and Fusobacterium nucleatum with CRC relative to controls. In addition, we identified several microbial species differentially enriched in young colorectal cancer patients. Studies targeting the young CRC patients are warranted to elucidate underlying preclinical mechanisms.